Understanding the Impact of Extrusion Treatment on Cereals: Insights from Alterations in Starch Physicochemical Properties and In Vitro Digestion Kinetics - Yufei Zhao; Xiuquan Dang; Honglin Du; Dapeng Wang; Jiaxuan Zhang; Rujie Liu; Zhenying Ge; Zewei Sun; Qingzhen Zhong (Animals)
In this study, three samples were randomly selected from corn, wheat, and broken rice before and after extrusion for electron microscope scanning, Fourier transform infrared spectral analysis, and in vitro digestion to investigate the impact of extrusion on physicochemical characteristics and starch digestion kinetics of cereals. The cereals used for extrusion were sourced identically before and after the process, with each analysis conducted in triplicate. The results showed that the extrusion compromised the physical structure of cereal, resulting in loose structure arrangement, and the ratio of Fourier transform infrared spectral absorbance at wavelength 1047 cm−1 and 1022 cm−1, which characterized the short-range order of starch, was significantly reduced (p < 0.05). In addition, the proportion of rapidly digestible starch (RDS), the velocity parameter k of digestive kinetics and the predicted glycemic index of cereals were significantly increased by extrusion (p < 0.05). Digestibility kinetics showed a total increase of 10.7%, 7.3%, and 5.4% for cereals, along with a sharp rise in digestion rate within the first 15 minutes. The findings revealed that the compromising of starch’s structural integrity and the increase in proportion of RDS not only enhanced overall starch digestibility, but also significantly accelerated its digestion, particularly during the initial 15 min of intestinal digestion.